2021
DOI: 10.1177/1097184x21990737
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Inequalities? Parents’ Sleep, Anxiety, and Calm during the COVID-19 Pandemic in Australia and the United States

Abstract: As a cultural ideal, hegemonic masculinity positions men as breadwinners in the gender order-a position that systematically benefits men and disadvantages women. Because economic success is key to performing masculinity (Connell 2005), the COVID-19 pandemic and its economic fallout offer an opportunity to evaluate shifting gender dynamics amidst rapid changes in employment and domestic demands for heterosexual couples with children. Closures of schools, daycare facilities, and workplaces around the world shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 6 publications
4
48
0
Order By: Relevance
“…On the other hand, research shows that mothers, on average, still perform more housework than fathers and spend a higher number of hours on home‐schooling and childcare responsibilities (Carlson et al., 2020; Ruppanner, Tan et al., 2021). To this point, a report by McKinsey & Company (2020) showed that during COVID‐19, “mothers are more than three times as likely as fathers to be responsible for most of the housework and caregiving” (p. 18).…”
Section: The Pandemic and Gender Inequality: Changes To Work And Familymentioning
confidence: 99%
“…On the other hand, research shows that mothers, on average, still perform more housework than fathers and spend a higher number of hours on home‐schooling and childcare responsibilities (Carlson et al., 2020; Ruppanner, Tan et al., 2021). To this point, a report by McKinsey & Company (2020) showed that during COVID‐19, “mothers are more than three times as likely as fathers to be responsible for most of the housework and caregiving” (p. 18).…”
Section: The Pandemic and Gender Inequality: Changes To Work And Familymentioning
confidence: 99%
“…Before COVID‐19 became a universal pandemic, women were doing more unpaid care and domestic work than men in both countries (Craig & Mullan, 2010). During the start of the pandemic, these divisions worsened with initial evidence showing mothers assumed a larger share of the domestic work in the US (Carlson et al., 2020; Ruppanner et al., 2021) and Australia (Craig & Churchill, 2021; Ruppanner et al., 2021). Amongst those in the US who have maintained employment, married mothers reduced work time across all child‐ages and even when they and their partner could work from home (Collins et al., 2020).…”
Section: A Gendered Pandemic: a Comparison Of Australia And Usmentioning
confidence: 99%
“…Whether this translates into women, and in particular, mothers reporting greater financial worry and emotional strain is not yet to be fully understood. Existing pandemic research shows US mothers carrying more domestic work and employment disruptions reported greater anxiety and poorer sleep than US fathers and Australian parents (Ruppanner et al., 2021). However, little is known about whether these experiences replicate for the childless population and, importantly, to what extent is heightened poor emotional health is driven by financial worry.…”
Section: A Gendered Pandemic: a Comparison Of Australia And Usmentioning
confidence: 99%
“…The use of lockdowns to attempt to mitigate the transmission of COVID-19 in communities increased the household and child-rearing demands of both men and women [25]. A global study of academics found that this resulted in decreased time available to devote to research across the board; however, this was disproportionately experienced by women [26].…”
Section: Introductionmentioning
confidence: 99%